On-Line and Real-Time Analysis of Moisture Content in Activated Carbon Powder by X-Ray Scattering Technique - Suk Choi, Yong; Hwang, Jaesik; Kim, Jong-Yun (Asian Journal of Chemistry, 2014)
On-line and real-time analyses of moisture in activated carbon powders were performed using a pilot-scale X-ray monitoring system. The system was composed of an X-ray tube generator as an X-ray source, a cadmium telluride (CdTe) X-ray detector and a circular rotating disk to simulate real processes. Total X-ray scattering intensities from the powder samples moving at a speed of 4 m/min were measured with a very short counting time of 0.1 s. The wet powder samples with various moisture contents were successfully monitored in real-time using our in-house built X-ray scattering measurement system.